Miller Fisher Syndrome- a Case Report and Review of Literature (Bangladesh Journal of Neuroscience, 2016)
Background and Objective:: Miller Fisher syndrome (MFS) is a variant of Guillan Barre syndrome characterized by ophthalmoplegia, ataxia and areflexia. Although self-limiting disease course is expected, disease modifying treatment options for MFS are no different than for GBS and include intravenous immune globulin (IVIG) and plasmapheresis. Here, we report a case of MFS presented with bilateral ptosis, ophthalmoplegia, ataxia with quadriparesis and normal NCS. PatientMethods: A 14- year-old young boy was admitted to our hospital with the complaints of double vision, vertigo, difficulty in walking, imbalance. He had no diarrhea or upper respiratory tract infection prior to this illness. On neurological examination, he had limited ability to move his eyes up and out, had bilateral ptosis, ataxia. The muscle strength was mildly impaired. The plantar reflexes were flexor and the deep tendon reflexes were absent.Results: The blood laboratory, CT and brain MRI were normal. In the first sample of CSF, there was no change. Subsequent sample after 14 days revealed high protein with albuminocytological dissociation. The NCS and EMG were normal. Anti GQ 1b antibody was negative. He showed marked improvement with conservative management.Conclusion: MFS is a rare disease that must be diagnosed with the clinical findings and in the following days the diagnosis can be supported by the laboratory findings.Bangladesh Journal of Neuroscience 2016; Vol. 32 (1): 47-51